2010
DOI: 10.5021/ad.2010.22.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Malondialdehyde and Glutathione Levels in Vitiligo Patients

Abstract: Background:Vitiligo is an acquired and progressive hypomelanotic disease that manifests as circumscribed depigmented patches on the skin. Although the precise mechanism remains to be elucidated, an imbalance of the oxidant/antioxidant system has been proposed as an important etiologic mechanism. Objective: The objective of this study was to evaluate the oxidant/antioxidant status of vitiligo patients at the erythrocyte level. Methods: Fifty-three vitiligo patients and 65 phototype-, age-, and sex-matched healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
3
18
0
1
Order By: Relevance
“…Erythrocytes are considered to be a more accurate eflection of oxidative or antioxidative status than plasma or serum, as the erythrocyte is prone to oxidative reactions. 16 Our subgroup analysis in erythrocytes showed a significant association between higher SOD level and vitiligo, which agreed with the result from the analysis stratified by stage. No association was seen between vitiligo and erythrocyte MDA level, which did not concur with the results from the overall meta-analysis and all other subgroup analyses; however, only two studies were included in this subgroup analysis, which may have led to the unreliable results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Erythrocytes are considered to be a more accurate eflection of oxidative or antioxidative status than plasma or serum, as the erythrocyte is prone to oxidative reactions. 16 Our subgroup analysis in erythrocytes showed a significant association between higher SOD level and vitiligo, which agreed with the result from the analysis stratified by stage. No association was seen between vitiligo and erythrocyte MDA level, which did not concur with the results from the overall meta-analysis and all other subgroup analyses; however, only two studies were included in this subgroup analysis, which may have led to the unreliable results.…”
Section: Discussionsupporting
confidence: 91%
“…Decreased SOD activity could be responsible for the increase of superoxide radicals, which may in turn explain the increased level of MDA. Erythrocytes are considered to be a more accurate eflection of oxidative or antioxidative status than plasma or serum, as the erythrocyte is prone to oxidative reactions . Our subgroup analysis in erythrocytes showed a significant association between higher SOD level and vitiligo, which agreed with the result from the analysis stratified by stage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Markers of lipid peroxidation are therefore considered as good measures of oxidative stress . Seventeen different studies including 745 patients clearly demonstrate increased MDA concentrations in patients with vitiligo . Five additional studies (2119 patients) confirmed increased lipid peroxidation in erythrocytes of patients with vitiligo …”
Section: Resultsmentioning
confidence: 99%